2010
DOI: 10.5424/sjar/2010082-1198
|View full text |Cite
|
Sign up to set email alerts
|

Storage behaviour of ‘Reinette du Canada’ apple cultivars

Abstract: Apple (Malus domestica Borkh) cultivars 'Reinette du Canada' (RC) and 'Reinette Grise du Canada' (RG) have been declared throughout the European Community as protected designation of origin (PDO) 'Manzana Reineta del Bierzo'. The aim of this research was to find out the influence of storage technique on quality of PDO apple cultivars 'RC' and 'RG', and to evaluate the absence of traditional post-harvest treatments in these high quality cultivars in order to reduce pesticide residues in fruit. Apples were kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…In the second year, the effect of Ca solution on fruits TA was significant after three months storage and fruits received Folical had more TA Agricultural Research & Technology: Open Access Journal than control (Figure 7). As previous findings have reported [35,36] the amount of TA in the fruits reduced during storage. This reduction did not have a clear trend between control and treated fruits.…”
Section: Titratable Acidity After Storagesupporting
confidence: 80%
See 1 more Smart Citation
“…In the second year, the effect of Ca solution on fruits TA was significant after three months storage and fruits received Folical had more TA Agricultural Research & Technology: Open Access Journal than control (Figure 7). As previous findings have reported [35,36] the amount of TA in the fruits reduced during storage. This reduction did not have a clear trend between control and treated fruits.…”
Section: Titratable Acidity After Storagesupporting
confidence: 80%
“…In the second year, late-season spray had the higher TA compared to the early-season spray (Figure 6). Various results have been reported on the effect of calcium on the amount of TA [25,36,37]. In our study (Table 2), no specific trend was observed and the effect of compounds on TA levels varied depending on the foliar application time.…”
Section: Titratable Acidity At Harvestcontrasting
confidence: 47%
“…Five triploids accessions are labelled as 'Reineta'. The notable presence of 'Reineta' accessions in several municipalities is explained by two facts: first, its ethnobotanical importance in the past (Guerra et al 2010) and second, its medium to late blooming (Pina 2005). As a result, it is possible to speculate that 'Reineta' might be suitable in mountainous and cold environments as it was suggested (Pina et al 2014).…”
Section: Ploidy Levelmentioning
confidence: 99%
“…'Reineta', 'Reinette du Canada' and 'Reinette Grise du Canada' apple cultivars are traditional fruits of El Bierzo (León, northwest of Spain) (Guerra et al, 2010). 'Reineta' is one of the two Spanish apples that is protected throughout the community as a Protected Designation of Origin (PDO), 'Manzana Reineta del Bierzo' (Commission Regulation (EC) Nº 2601/2001).…”
Section: Introductionmentioning
confidence: 99%